ON THE EXPEDIENCY AND DIRECTIONS OF IMPROVING THE METHODOLOGY OF TEACHING STUDENTS MATERIAL OF THE CONTENT LINE "FUNCTIONS AND THEIR GRAPHS" - Hoda, Tetiana; Shkolnyi, Oleksandr (Physical and Mathematical Education, 2022)
Formulation of the problem. Improving the methodology of teaching students the material of the content line "Functions and their graphs" is currently a relevant problem, because knowledge of the properties of elementary functions contributes to the formation of students’ adequate worldview based on acquired general and subject competencies. The functions have a lot of practical applications and are used during studying the material of the school course of physics, chemistry, biology, computer science, etc. Also, the material of the content line "Functions and their graphs" is very important for the successful compilation of external independent assessment of the quality of knowledge in mathematics. In addition, the need to improve the methodology of teaching students functions is confirmed by the results of the International Comparative Survey PISA 2018, statistical reports of the Ukrainian Center for Educational Quality Assessment on mathematics testing, and surveys of mathematics teachers. Materials and methods. To achieve our goal, we use the theoretical method of analysis of the methodological literature on the subject. We also use some empirical methods: our own survey using Google forms, monitoring the learning process in secondary schools, and analysis of student achievement. In this article, we also use a set of methods of scientific knowledge: comparative analysis to clarify different views on the problem; systematization, and generalization in order to draw conclusions and formulate recommendations for improving the methodology of teaching students the material of the content line "Functions and their graphs"; generalization of pedagogical experience and observations of the authors. Results. The hypothesis concerning the expediency of improvement of a technique of training of students of secondary schools of a material of the content line "Functions and their graphs" is formulated. In order to confirm this hypothesis and outline the directions of such improvement with using of modern information and communication technologies, a survey of teachers has been conducted. The poll has been conducted anonymously and online using Google forms. About 100 teachers with different teaching experience and qualifications took part in the survey, but most of them have been working at the school for more than 15 years. The survey showed that most respondents often or constantly use modern computer technologies in the educational process, and are convinced of the need to improve the methodology of teaching students the material of the content line "Functions and their graphs". One of the directions of such improvement, they believe the use of modern computer technologies in mathematics lessons, as well as the development of appropriate didactic materials and guidelines for their application. Conclusions. To improve the methodology of teaching students the material of the content line "Functions and their graphs" it seems natural to use modern computer technologies. Teachers are currently actively using modern electronic tools for teaching mathematics, but need methodological support for their application in the educational process. In particular, this applies to studying the content line "Functions and their graphs": there is a need to develop ready-made didactic materials and to create guidelines for using information technology to study the material of this content line, which will use modern computer tools in the educational process more effectively.